Sclerosing Angiomatoid Nodular Transformation: Laparoscopic Splenectomy as Therapeutic and Diagnostic Approach at the Same Time. (8th May 2018) - Cipolla, Calogero; Florena, Ada Maria; Ferrara, Gabriella; Di Gregorio, Riccardo; Unti, Elettra; Giannone, Antonino G.; Lazzaro, Luigi A.; Graceffa, Giuseppa; Pantuso, Gianni
Abstract : Introduction . Sclerosing angiomatoid nodular transformation (SANT) of the spleen is a rare benign vascular lesion with unknown etiopathogenesis and with definite features of imaging, histopathology, and immunohistochemistry. It was first described by Martel et al. in 2004, and to date, only 151 cases have been reported. Case Description . We report a case of SANT of the spleen detected in a 66-year-old Caucasian, without comorbidities, presented to our department with epigastric pain. We, also, presented a review of the literature. Conclusions . SANT is a benign incidentally vascular condition in the majority of cases. The wide age and gender distribution in our review is in accordance with that in previous studies in English literature. In our opinion, splenectomy is the choice treatment because it is at the same time diagnostic and therapeutic in a definitive way.